Perceptions about FinTech: New evidences from the Middle East - Syed Akmal; Mohammad Talha; Syed Mohammad Faisal; Moid Uddin Ahmad; Ahmad Khalid Khan (Cogent Economics & Finance, 2023)
The study aimed to analyze the perceptions of FinTech in the Middle East region, specifically its usage, and performance. To attain this objective, a strategy employed on surveys as the primary data acquisition method was implemented. The survey was conducted between November 2021 and February 2022, which allowed the researcher to gather comprehensive data from respondents during this period. In order to ensure the descriptive nature of the study, cross-sectional research was employed in its design. This design allowed the researcher to gather data at a single point in time, which was appropriate for the scope of this study. The researcher utilized a questionnaire during the inquiry to elicit information for data collection purposes. The questionnaire was designed to include semi-structured questions, which allowed the respondents to provide detailed information on their perceptions of FinTech. This study employed a survey-based technique to analyze the perceptions of FinTech in the Middle East region. Using a cross-sectional design and semi-structured questions allowed the researcher to achieve the descriptive nature of the research. Additionally, cross-tab analysis and SPSS provided an in-depth understanding of the data collected. The findings from the analysis suggest that FinTech enhances the performance of financial institutions and that digital banking is the best feature of FinTech across all customer groups.
Keywords: 330; business performance; financial institutions; FinTech; perception